Improving emotional health and self-esteem of Malaysian adolescents living in orphanages through life skills education program: a multi-centre randomized control trial - Mohammadzadeh, Marjan; Awang, Hamidin; Ismail, Suriani; Kadir @ Shahar, Hayati (Public Library of Science, 2019)
Generally speaking, institutionalised children and adolescents are at greatly increased risk of serious mental and behavioural problems, up to seven times more than their peers. Life skills- based interventions using peer enforcement have been introduced as effective program to improve adolescents’ emotional and behavioral health. Therefore, the current randomized control study aimed to determine, if a life skills-based intervention could improve the emotional health and self-esteem among Malaysian adolescents in orphanages. Overall, 271 male and female adolescents (13–18 years old) from 8 orphanages in Klang valley, Malaysia participated in the study. Comparing the intervention to control group within 3 points of time, the finding of the study showed that immediately after finishing the interventional sessions (post-test), the mean scores of depression (F = 33.80, P<0.001, η2 = 0.11), anxiety (F = 6.28, P = 0.01, η2 = 0.02), stress (F = 32.05, P<0.001, η2 = 0.11) and selfesteem (F = 54.68, P<0.001, η2 = 0.17) were significantly decreased compared to the pretest values. However, there was no significant difference between two groups in the depression mean scores (F = 2.33, P = 0.13). Regarding to the interaction between group and test a significant change was seen in the mean score of all 4 variables including depression (F = 31.04, P<0.001, η2 = 0.10), anxiety (F = 14.21, P<0.001, η2 = 0.05), stress (F = 15.67, P<0.001, η2 = 0.06) and self-esteem (F = 13.29, P<0.001, η2 = 0.05). Furthermore, except depression (Δmean = -1.37, P<0.001), no significant difference was seen between study variables’ mean scores between post- and follow-up test (p>0.001). These results provide preliminary approve for LSE to enhance emotional health and self-esteem in orphanages.